(untitled) - Kellerhals, B. Philipp (Berlin,New York, 2004)
The modern field of asset pricing asks for sound pricing models grounded on the theory of financial economics as well as for accurate estimation techniques when it comes to empirical inferences of the specified model. This book provides a canonical framework that shows how to bridge the gap between the continuous-time pricing practice in financial engineering and the capital market data inevitably only available at discrete-time intervals. Starting with a comprehensive treatment of the particular stochastic modeling and econometric estimation framework, the main parts of the book cover applications to risky assets traded on the markets for funds, fixed-income products and electricity derivatives. The second edition newly incorporates the financial modeling chapter which elaborates on the vital PDE- and EMM-approaches. The reorganized and improved text further integrates the latest research contributions in the three covered application fields.
Keywords: Finance,Assets (Accounting),Tài chính; Mathematical models, Prices,Econometric models,Mô hình toán